2007
DOI: 10.1007/s10038-007-0116-7
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal kinesigenic choreoathetosis (PKC): confirmation of linkage to 16p11-q21, but unsuccessful detection of mutations among 157 genes at the PKC-critical region in seven PKC families

Abstract: Paroxysmal kinesigenic choreoathetosis (PKC) is a paroxysmal movement disorder of unknown cause. Although the PKC-critical region (PKCCR) has been assigned to the pericentromeric region of chromosome 16 by several studies of families from various ethnic backgrounds, the causative gene has not yet been identified. In the present study, we performed linkage and haplotype analysis in four new families with PKC, as well as an intensive polymerase chain reaction (PCR) based mutation analysis in seven families for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…[2][3][4] In our previous study, we performed a genome-wide linkage and haplotype analysis and defined disease locus within the pericentromeric region of chromosome 16. 1,5 Subsequently, we performed mutation analysis on 229 genes between D16S3131 and D16S503; however, we failed to identify the causative gene. 5,6 Recently, Chen et al 7 identified truncating mutations within protein-rich transmembrane protein 2 (PRRT2) in eight HanChinese families with histories of PKD using whole-exome sequencing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In our previous study, we performed a genome-wide linkage and haplotype analysis and defined disease locus within the pericentromeric region of chromosome 16. 1,5 Subsequently, we performed mutation analysis on 229 genes between D16S3131 and D16S503; however, we failed to identify the causative gene. 5,6 Recently, Chen et al 7 identified truncating mutations within protein-rich transmembrane protein 2 (PRRT2) in eight HanChinese families with histories of PKD using whole-exome sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Subsequently, we performed mutation analysis on 229 genes between D16S3131 and D16S503; however, we failed to identify the causative gene. 5,6 Recently, Chen et al 7 identified truncating mutations within protein-rich transmembrane protein 2 (PRRT2) in eight HanChinese families with histories of PKD using whole-exome sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies narrowed down the critical region for PKD/ ICCA. However, conventional genetic methods including linkage and haplotype analysis as well as Sanger sequencing of more than 150 genes located around the critical region in chromosome 16 were not able to identify the associated gene [ 25 ]. Only with the advent of whole-exome sequencing it was possible to demonstrate heterozygous mutations in PRRT2 as a cause of PKD [ 26 -29 ].…”
Section: Genetics Of Pkdmentioning
confidence: 99%
“…Despite the identification of the chromosome 16 BFIE/ICCA/PKD locus in 1997 and the subsequent extensive sequencing of candidate genes within the region,19 21 the causative gene was not identified for many years. In 2011, Chen and colleagues4 successfully employed a strategy combining linkage analysis and whole exome sequencing to identify mutations in an uncharacterised gene, PRRT2 , in eight Chinese families with PKD.…”
Section: Identification Of Mutations In Prrt2mentioning
confidence: 99%